Social casework in the fifties. Selected articles, 1951-1960. C. Kasius, editor. [With contribs of M.W. Pumphrey, M.J. McCormick, G. Hamilton a.o.] (Family Service Association of America, 1962)
With index. Repr.: Social casework.